2021
DOI: 10.1007/978-3-030-72651-5_17
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 in Retail: A Systematic Literature Review

Abstract: The objective of this research is to discuss the state-of-the-art with regard to the influence of COVID-19 in retail, especially in the light of the economic, social and health perspectives. To do so, we carried out a systematic literature review, a technique that allows an efficient description of the literature and that made it possible to provide a holistic perspective of the phenomenon trough the interpretation of relevant published articles. The results showed the sector had to find new measures to mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Hoekstra & Leeflang (2020) postulates that the prevalence of COVID led to the disruption of marketing strategies and policies. Studies have revealed that the retail operations have been disrupted by the pandemic (Delasay et al, 2022;Lopes & Reis, 2021). It is perhaps worth noting to highlight that this has been a difficult time of dealing with customers whose preferences changed a lot (Sheth, 2020) hence it became imperative that businesses adapt to best serve the evolving customer needs during pandemic and recession time (McKinsey & Company, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hoekstra & Leeflang (2020) postulates that the prevalence of COVID led to the disruption of marketing strategies and policies. Studies have revealed that the retail operations have been disrupted by the pandemic (Delasay et al, 2022;Lopes & Reis, 2021). It is perhaps worth noting to highlight that this has been a difficult time of dealing with customers whose preferences changed a lot (Sheth, 2020) hence it became imperative that businesses adapt to best serve the evolving customer needs during pandemic and recession time (McKinsey & Company, 2020).…”
Section: Introductionmentioning
confidence: 99%